Meningkatkan Hasil Belajar Siswa di SD Negeri Tanjungsari dengan Model Experiential Learning - Shinta Futichatul ‘Aini (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this study was to find out how the effect of using the Experiential Learningmodel as a means to improve student learning outcomes at Tanjungsari Elementary Schoolduring the Covid-19 pandemic. This research uses Classroom Action Research (CAR) with aquantitative approach. The subjects in this study were the 5th grade students of SD NTanjungsari, totaling 22 children. However, the author only took a sample of 5 children dueto the current pandemic situation which did not allow the author to collect all children in oneclass. The author uses an essay test to measure students' abilities. The average score of Cycle1 obtained by students is 71 and the average score of Cycle 2 obtained by students is 82. Itcan be seen that there is a significant increase in scores after and before conducting researchusing the Experiential Learning model. The results of this study indicate that theExperiential Learning model has a positive effect on increasing student learning outcomes.